English Speakers Can Infer Pokémon Types Based on Sound Symbolism - Kawahara, Shigeto; Godoy, Mahayana C.; Kumagai, Gakuji (Frontiers in Psychology, 2021)
Sound symbolism, systematic associations between sounds and meanings, is receiving increasing attention in linguistics, psychology and related disciplines. One general question that is currently explored in this research is what sorts of semantic properties can be symbolically represented. Against this background, within the general research paradigm which explores the nature of sound symbolism using Pokémon names, several recent studies have shown that Japanese speakers associate certain classes of sounds with notions that are as complex as Pokémon types. Specifically, Japanese speakers associate (1) sibilants with the flying type, (2) voiced obstruents with the dark type, and (3) labial consonants with the fairy type. These sound symbolic effects arguably have their roots in the phonetic properties of the sounds at issue, and hence are not expected to be specific to Japanese. The current study thus addressed the question of whether these sound symbolic associations hold with native speakers of English. Two experiments show that these sound symbolic patterns patterns were very robustly observed when the stimuli were presented in pairs; when the stimuli were presented in isolation, the effects were also tangible, although they are not as robust. We conclude that English speakers can associate certain types of sounds to particular Pokémon types, with an important caveat that we observed a clear task effect. Overall the current results lend some credibility to the hypothesis advanced by Shih et al. (2019) that those attributes that may play a role in their survival are actively signaled by sound symbolism